Method for producing orally disintegrating tablet
Patent Information
- Application Number
- JP2023177803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2026-10-16
AI Technical Summary
Oral dissociation phenotypes are easily damaged by impact when manufactured, packaged, transported or packaged in hospitals, resulting in fragile and fragile surfaces, making them difficult to increase their strength.
The surface agent is produced by using a wet granulation solution containing a wet granulation solution, which is obtained by wet granulation cellulose cell loss, ensuring that the cellulose cell loss content in the surface agent reaches 2.0% or higher, thereby increasing the strength of the surface agent.
It improves the strength of oral dissociated phenolic agents to prevent damage and breakage caused by impact, and ensures the stability of the phenolic agents during manufacturing, packaging, transportation and in-hospital packaging.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an orally disintegrating tablet. [Background technology]
[0002] Orally disintegrating tablets (OD tablets) have the property of disintegrating quickly in the mouth, and are one of the dosage forms that make it easier for patients with poor swallowing ability to take medicines. In addition, depending on the disease, it is possible to reduce the intake of fluids when taking medicine, making it a useful dosage form for medical institutions.
[0003] Crystalline cellulose is produced by partially depolymerizing α-cellulose obtained from fibrous plants with acid and purifying it, and is widely used as an additive (eg, excipient) for orally disintegrating tablets.
[0004] For example, Patent Document 1 describes a method for producing an orally disintegrating tablet, which includes a step of stirring and granulating a drug-containing powder while spraying or dropping an aqueous solution containing a monosaccharide onto the powder, followed by drying to obtain drug granulated particles, and a step of compressing the obtained drug granulated particles or a mixture of the drug granulated particles and other tablet ingredients. The patent document also describes that crystalline cellulose is blended with the drug-containing powder, and that the blending of a small amount of crystalline cellulose has the property of improving the friability of tablets.
[0005] In addition, Patent Document 2 states that the bulk density is 0.23 g / cm 3 A mixture containing the following crystalline cellulose and sugar alcohol is wet granulated with a liquid in which pregelatinized starch is dissolved or dispersed, or a mixture having a bulk density of 0.23 g / cm 3 The present invention describes a method for producing an orally disintegrating tablet, which includes a step of wet-granulating a mixture containing the following crystalline cellulose, sugar alcohol, and pregelatinized starch with water, drying the resulting granules, mixing the resulting granules with a powdered or granulated drug, and, if desired, an additive, and compressing the mixture into a tablet. The present invention also describes a method for producing an orally disintegrating tablet, which includes a step of wet-granulating a mixture containing the following crystalline cellulose, sugar alcohol, and pregelatinized starch with water, drying the resulting granules, mixing the resulting granules with a powdered or granulated drug, and, if desired, an additive, and compressing the mixture into a tablet. 3A mixture containing the following crystalline cellulose and sugar alcohol is wet granulated with a liquid in which pregelatinized starch is dissolved or dispersed, or a powdered drug, a bulk density of 0.23 g / cm 3 The following describes a method for producing an orally disintegrating tablet, which includes a step of wet granulating a mixture containing crystalline cellulose, a sugar alcohol, and pregelatinized starch with water, drying the granules obtained, optionally mixing them with other additives, and compressing the mixture into a tablet.
[0006] In Patent Documents 1 and 2, microcrystalline cellulose is contained in the raw material to be wet granulated. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2011-037840 A [Patent Document 2] International Publication No. 2013 / 161823 Summary of the Invention [Problem to be solved by the invention]
[0008] Impacts during manufacturing, packaging, transportation, packaging in hospitals, etc. (e.g., impacts from tablet packaging machines) can cause damage such as chipping and cracking in the orally disintegrating agent, which can impair the appearance of the orally disintegrating agent. Orally disintegrating tablets are more fragile than general tablets and are therefore more susceptible to damage such as chipping and cracking. Therefore, there is a demand for improving the strength of orally disintegrating tablets.
[0009] Therefore, an object of the present invention is to provide a method for producing an orally disintegrating tablet with improved strength. [Means for solving the problem]
[0010] The present inventors have discovered that in a method for producing orally disintegrating tablets by tableting a tableting raw material containing a granulation product obtained by wet granulation, the strength of the orally disintegrating tablets produced can be improved by performing wet granulation using a granulation liquid containing a wet-grinding liquid obtained by wet-grinding crystalline cellulose such that the amount of crystalline cellulose derived from the wet-grinding liquid contained in the orally disintegrating tablet is 2.0 mass% or more based on the mass of the orally disintegrating tablet.
[0011] The present invention is based on the above findings and includes the following inventions. [1] The following steps: (a) preparing a granulation liquid containing a wet-grinding liquid obtained by wet-grinding crystalline cellulose; (b) wet-granulating a first granulation raw material containing a drug and an additive with the granulation liquid to obtain a first granulation product, or wet-granulating a second granulation raw material containing an additive but not a drug with the granulation liquid to obtain a second granulation product; and (c) A step of compressing the first tableting raw material containing the first granule and optionally an additive, or the second tableting raw material containing the second granule, a drug and optionally an additive, to obtain an orally disintegrating tablet. A method for producing an orally disintegrating tablet, comprising: The above-mentioned production method, wherein the amount of crystalline cellulose derived from the wet-grinding liquid contained in the orally disintegrating tablet is 2.0 mass% or more based on the mass of the orally disintegrating tablet. [2] The method according to [1], wherein the median diameter D50 of the crystalline cellulose in the wet-grinding liquid is 25 μm or less. [3] The method according to [1] or [2], wherein the orally disintegrating tablet has a friability of 1.0% or less. [4] The method according to any one of [1] to [3], wherein the first or second granulation raw material contains an excipient and a disintegrant as the additives. [5] The method according to [4], wherein the excipient comprises D-mannitol. [6] The method according to [4] or [5], wherein the disintegrant comprises one or more selected from the group consisting of crospovidone, low-substituted hydroxypropyl cellulose, and croscarmellose sodium. [7] The method according to any one of [1] to [6], wherein the first or second tableting raw material contains a lubricant as the additive. [8] The method of manufacturing according to [7], wherein the lubricant comprises magnesium stearate. Effect of the Invention
[0012] The manufacturing method of the present invention can manufacture an orally disintegrating tablet with improved strength. The orally disintegrating tablet manufactured by the manufacturing method of the present invention has improved strength, and therefore can prevent damage to the orally disintegrating agent (e.g., chipping, cracking, etc.) caused by impacts during manufacturing, packaging, transportation, packaging in hospitals, etc. (e.g., impacts from a tablet packaging machine). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <Orucodisintegrating tablets> Hereinafter, an orally disintegrating tablet produced by the method for producing an orally disintegrating agent according to the present invention will be described. Note that two or more of the embodiments described in this specification can be combined.
[0014] <Drugs> The orally disintegrating agent contains a drug.
[0015] The drug is an active ingredient of the orally disintegrating tablet. The drug is not particularly limited as long as it is an orally administrable drug, and can be appropriately selected in consideration of the subject of administration, the disease to be treated or prevented, etc.
[0016] Examples of drugs include antipyretic, analgesic and anti-inflammatory drugs such as aspirin, acetaminophen, ibuprofen, diclofenac sodium, ethenzamide and indomethacin; psychoneurotic drugs such as etizolam, amitriptyline hydrochloride and sulpiride; hypnotic and sedative drugs such as amobarbital, alprazolam, flurazepam hydrochloride and diazepam; perampanel drugs such as istradeferin, levodopa, amantadine hydrochloride, trihexyphenidyl hydrochloride and piroheptine hydrochloride. Drugs for treating Kinson's disease; antiepileptic drugs such as sodium valproate, nitrazepam, phenytoin, etc.; antitussives such as pentoxinverin citrate, etc.; expectorants such as ambroxol hydrochloride, L-methylcysteine hydrochloride, etc.; gastrointestinal motility improvers such as domperidone, etc.; bronchodilators such as clenbuterol hydrochloride, procaterol hydrochloride, etc.; antihistamines such as homochlorcyclizine hydrochloride, clemastine fumarate, chlorpheniramine maleate, etc.; ubidecarenone, Cardiac stimulants such as aminophylline and etilefrine hydrochloride; antiarrhythmic agents such as atenolol and pindolol; diuretics such as spirolactone, trichlormethiazide and furosemide; antihypertensive agents such as todralazine hydrochloride, nicardipine hydrochloride and hydralazine hydrochloride; vasoconstrictors such as dihydroergotamine mesylate; vasodilators such as benidipine hydrochloride, diltiazem hydrochloride and isosorbide dinitrate; antihyperlipidemic agents such as clinofibrate and nicomol; anethole Examples of the drug include cholagogues such as trithione and chenodeoxycholic acid, antibiotics such as paromomycin sulfate, amoxicillin, cefaclor, cephalexin, acetylspiramycin, and minocycline hydrochloride, skeletal muscle relaxants such as chlorphenesin carbamate and chlormezanone, autonomic nerve agents such as valethamate bromide and tofisopam, antispasmodics such as afloqualone, and antiulcer drugs such as cetraxate hydrochloride, pirenzepine hydrochloride, and famotidine. One drug may be used alone, or two or more drugs may be used in combination.
[0017] In one embodiment, the drug comprises istradeferin.
[0018] In another embodiment, the drug comprises domperidone.
[0019] In yet another embodiment, the drug comprises ethenzamide.
[0020] The amount of the drug contained in the orally disintegrating tablet is, for example, 0.1% by mass or more and 20% by mass or less based on the mass of the orally disintegrating tablet. When the orally disintegrating tablet contains one type of drug, the "amount of drug" means the amount of that one type of drug, and when the orally disintegrating tablet contains two or more types of drugs, the total amount of those two or more drugs.
[0021] <Crystalline Cellulose> The oral disintegrant includes microcrystalline cellulose.
[0022] Microcrystalline cellulose is a type of excipient. However, the use (function) of crystalline cellulose is not limited to that of an excipient.
[0023] At least a part of the crystalline cellulose contained in the orally disintegrating tablet is derived from the wet-grinding liquid prepared in step (a) and contained in the granulation liquid used in step (b). The entire crystalline cellulose contained in the orally disintegrating tablet may be derived from the wet-grinding liquid prepared in step (a) and contained in the granulation liquid used in step (b).
[0024] In order to improve the strength of the orally disintegrating tablet and effectively prevent the breakage of the orally disintegrating agent due to impact during production, packaging, transportation, and packaging in hospitals, the amount of crystalline cellulose derived from the wet grinding liquid contained in the orally disintegrating agent is preferably 2.0% by mass or more, more preferably 2.5% by mass or more, and even more preferably 3.0% by mass or more, based on the mass of the orally disintegrating tablet. The upper limit of the amount of crystalline cellulose derived from the wet grinding liquid contained in the orally disintegrating agent can be appropriately adjusted depending on the amount of the drug, the amount of other additives, etc., and is, for example, 20% by mass or less.
[0025] The orally disintegrating tablet may contain crystalline cellulose not derived from the wet-grinding liquid contained in the granulation liquid prepared in step (a) and used in step (b). The amount of crystalline cellulose not derived from the wet-grinding liquid contained in the orally disintegrating agent is, for example, 0% by mass or more and 20% by mass or less based on the mass of the orally disintegrating tablet.
[0026] <Additives other than crystalline cellulose> The oral disintegrant contains additives other than crystalline cellulose.
[0027] The additive other than crystalline cellulose can be appropriately selected from the additives generally used in tablets.The additive other than crystalline cellulose can be, for example, excipient, disintegrant, lubricant, colorant, sweetener, flavoring, flavoring, stabilizer, fluidizing agent, etc.The additive other than crystalline cellulose can be used alone or in combination of two or more.
[0028] Examples of excipients include sugars, sugar alcohols, celluloses, starches, inorganic salts, etc. Examples of sugars include lactose, lactose hydrate, sucrose, maltose, sucrose, glucose, etc. Examples of sugar alcohols include mannitol, sorbitol, erythritol, maltitol, xylitol, etc. Examples of celluloses include low-substituted hydroxypropylcellulose, carmellose, carmellose calcium, croscarmellose sodium, etc. Examples of starches include corn starch, potato starch, rice starch, partially pregelatinized starch, pregelatinized starch, etc. Examples of inorganic salts include calcium monohydrogen phosphate, calcium dihydrogen phosphate, sodium dihydrogen phosphate, calcium phosphate, etc. The sugars and sugar alcohols may be D- or L-isomers, or a mixture of D- and L-isomers. Examples of preferred excipients include D-mannitol, etc. The excipients may be used alone or in combination of two or more.
[0029] In one embodiment, the excipient comprises D-mannitol.
[0030] The amount of excipient contained in the orally disintegrating tablet is, for example, 20% by mass or more and 97% by mass or less, based on the mass of the orally disintegrating tablet. The amount of excipient does not include the amount of crystalline cellulose. The amount of excipient means the amount of one excipient when the orally disintegrating tablet contains one type of excipient, and means the total amount of the two or more excipients when the orally disintegrating tablet contains two or more types of excipients. The same applies to the amount of other additives.
[0031] Examples of disintegrants include crospovidone, low-substituted hydroxypropyl cellulose, croscarmellose sodium, sodium carboxymethyl starch, carboxymethyl cellulose, calcium carboxymethyl cellulose, partially pregelatinized starch, starch, etc. From the viewpoint of high disintegration function, preferred disintegrants include crospovidone, low-substituted hydroxypropyl cellulose, croscarmellose sodium, etc. The disintegrants may be used alone or in combination of two or more.
[0032] In one embodiment, the disintegrant comprises crospovidone.
[0033] The amount of the disintegrant contained in the orally disintegrating tablet is, for example, from 0.5% by mass to 20% by mass, based on the mass of the orally disintegrating tablet.
[0034] Examples of lubricants include magnesium stearate, calcium stearate, talc, glycerin monostearate, light anhydrous silicic acid, sodium stearyl fumarate, and sucrose fatty acid esters (e.g., sucrose stearate, sucrose palmitate, sucrose oleate, sucrose laurate, etc.). Examples of preferred lubricants include magnesium stearate, sodium stearyl fumarate, etc. One type of lubricant may be used alone, or two or more types may be used in combination.
[0035] The amount of lubricant contained in the orally disintegrating tablet is, for example, 0.1% by mass or more and 5% by mass or less based on the mass of the orally disintegrating tablet.
[0036] Examples of colorants include yellow ferric oxide, titanium oxide, talc, ferric oxide, black ferric oxide, copper chlorophyll, sodium copper chlorophyllin, carbon black, medicinal charcoal, edible dyes, licorice extract, green tea powder, riboflavin, riboflavin butyrate, riboflavin sodium phosphate, octyldodecyl myristate, etc. Colorants may be used alone or in combination of two or more.
[0037] The amount of colorant contained in the orally disintegrating tablet is, for example, from 0.01% by mass to 10% by mass, based on the mass of the orally disintegrating tablet.
[0038] Examples of sweeteners include saccharin sodium, saccharin, aspartame, acesulfame potassium, dipotassium glycyrrhizinate, sucralose, stevia, thaumatin, etc. The sweeteners may be used alone or in combination of two or more.
[0039] The amount of the sweetener contained in the orally disintegrating tablet is, for example, from 0.01% by mass to 10% by mass, based on the mass of the orally disintegrating tablet.
[0040] Examples of the flavoring agent include aspartame, sucralose, acesulfame potassium, neotame, etc. The flavoring agent may be used alone or in combination of two or more kinds.
[0041] The amount of the flavoring agent contained in the orally disintegrating tablet is, for example, from 0.01% by mass to 10% by mass, based on the mass of the orally disintegrating tablet.
[0042] Examples of the flavoring include orange micron, strawberry micron, pineapple micron, peppermint micron, 1-menthol, etc. The flavoring may be used alone or in combination of two or more kinds.
[0043] The amount of flavor contained in the orally disintegrating tablet is, for example, from 0.01% by mass to 2% by mass, based on the mass of the orally disintegrating tablet.
[0044] Examples of the stabilizer include ascorbic acid, L-arginine, etc. The stabilizer may be used alone or in combination of two or more kinds.
[0045] The amount of the stabilizer contained in the orally disintegrating tablet is, for example, from 0.1% by mass to 10% by mass, based on the mass of the orally disintegrating tablet.
[0046] Examples of the fluidizing agent include hydrous silicon dioxide, light anhydrous silicic acid, magnesium aluminometasilicate, talc, etc. The fluidizing agent may be used alone or in combination of two or more kinds.
[0047] The amount of the glidant contained in the orally disintegrating tablet is, for example, from 0.1% by mass to 10% by mass, based on the mass of the orally disintegrating tablet.
[0048] The mass of each orally disintegrating tablet is, for example, from 80 mg to 220 mg.
[0049] Oral disintegrants disintegrate quickly in the oral cavity.
[0050] The disintegrability of the orally disintegrating agent can be evaluated based on the disintegration time of the orally disintegrating agent.
[0051] The disintegration time of the orally disintegrating agent is preferably 60 seconds or less, more preferably 40 seconds or less, and even more preferably 20 seconds or less. The disintegration time of the orally disintegrating agent can be measured according to the method described in the Examples.
[0052] The orally disintegrating tablet has improved strength, which makes it possible to prevent damage to the orally disintegrating agent (e.g., chipping, cracking, etc.) caused by impacts during production, packaging, transportation, packaging in hospitals, etc. (e.g., impacts from tablet packaging machines).
[0053] The strength of an oral disintegrant can be evaluated based on its hardness and friability.
[0054] The hardness of the orally disintegrating agent is preferably 40 N or more in order to improve the strength of the orally disintegrating tablet and effectively prevent the orally disintegrating agent from being damaged due to impact during production, packaging, transportation, packaging in hospitals, etc. The hardness of the orally disintegrating agent can be measured according to the method described in the Examples.
[0055] In order to improve the strength of the orally disintegrating tablet and effectively prevent the orally disintegrating agent from being damaged due to impact during production, packaging, transportation, packaging in hospitals, etc., the friability of the orally disintegrating tablet is preferably 1.0% or less, more preferably 0.4% or less, and even more preferably 0.2% or less. The friability of the orally disintegrating agent can be measured according to the method described in the Examples.
[0056] <Method of manufacturing orally disintegrating agent> The method for producing the orally disintegrating agent according to the present invention will be described below. Note that two or more of the embodiments described in this specification can be combined.
[0057] The method for producing the orally disintegrating agent according to the present invention comprises steps (a) to (c).
[0058] <Process (a)> Step (a) is a step of preparing a granulation liquid containing a wet-grinding liquid obtained by wet-grinding crystalline cellulose.
[0059] The wet-grinding liquid can be obtained by subjecting a grinding raw material containing crystalline cellulose and a dispersion medium to wet-grinding.
[0060] The amount of crystalline cellulose contained in the pulverized raw material is, for example, 1% by mass or more and 30% by mass or less based on the mass of the pulverized raw material.
[0061] The amount of the dispersion medium contained in the pulverized raw material is, for example, 70% by mass or more and 99% by mass or less, based on the mass of the pulverized raw material.
[0062] As the dispersion medium, for example, an aqueous medium such as water can be used, but it is preferable to use water, and it is more preferable to use purified water.
[0063] When the pulverized raw material is subjected to wet pulverization, the crystalline cellulose contained in the pulverized raw material is pulverized. In order to improve the strength of the orally disintegrating tablet and effectively prevent the breakage of the orally disintegrating agent caused by impact during production, packaging, transportation, and packaging in hospitals, the median diameter D50 of the crystalline cellulose in the wet pulverization liquid (i.e., the crystalline cellulose after wet pulverization) is preferably 25 μm or less. The lower limit of the median diameter D50 of the crystalline cellulose in the wet pulverization liquid can be appropriately adjusted, but is, for example, 10 μm or more.
[0064] The median diameter D50 of the crystalline cellulose in the pulverized raw material (that is, the crystalline cellulose before wet pulverization) is, for example, more than 25 μm and 170 μm or less.
[0065] The median diameter D50 is the particle size at which the cumulative volume is 50% in the volume-based particle size distribution obtained by the laser diffraction particle size distribution measurement method. The laser diffraction particle size distribution measurement method can be performed according to the conditions described in the Examples.
[0066] The wet grinding can be carried out using, for example, a ball mill, a microfluidizer, a starburst, a bead mill, or the like.
[0067] In one embodiment, the wet milling is carried out using a ball mill.
[0068] The material of the balls is, for example, high-purity alumina, zirconia, aluminum nitride, plastic, etc. The diameter of the balls is, for example, 1 mm or more and 40 mm or less. The filling amount of the balls is, for example, 20% or more and 40% or less based on the capacity of the grinding container (usually called a pot or drum) (see page 51 of "Ceramics Material Process", edited by Shirasaki Shinichi and Kato Akio, Ohmsha (1987)). The filling amount of the grinding raw material is, for example, 20% or more and 50% or less based on the capacity of the grinding container.
[0069] As the ball mill, for example, a rotary ball mill, a vibration ball mill, a planetary ball mill, or the like can be used.
[0070] In one embodiment, the ball mill is a rotary ball mill.
[0071] When a rotary ball mill is used, the rotation speed is, for example, 50 rpm or more and 1000 rpm or less. The time for wet grinding with the rotary ball mill is, for example, 5 hours or more and 72 hours or less.
[0072] The granulation liquid is prepared using the wet-grinding liquid. When preparing the granulation liquid, it is preferable that the dispersion state of the crystalline cellulose in the wet-grinding liquid is maintained. The wet-grinding liquid may be used as the granulation liquid as it is, may be used as the granulation liquid after being concentrated or diluted, or may be used as the granulation liquid after adding one or more additives. That is, the granulation liquid may be a granulation liquid containing the wet-grinding liquid, a granulation liquid containing a concentrated liquid or a diluted liquid of the wet-grinding liquid, or a granulation liquid containing the wet-grinding liquid or a concentrated liquid or a diluted liquid thereof and one or more additives.
[0073] In one embodiment, the wet milling liquid is used as the granulation liquid as is, i.e. the granulation liquid consists of the wet milling liquid.
[0074] In another embodiment, the wet-grinding liquid is used as the granulation liquid after addition of one or more additives, i.e. the granulation liquid is composed of the wet-grinding liquid and one or more additives.
[0075] For diluting the wet-grinding liquid, an aqueous medium such as water can be used, but it is preferable to use water, and it is more preferable to use purified water.
[0076] Specific examples of additives added to the wet-grinding liquid are the same as those described above. The additives may be used alone or in combination of two or more. The additives added to the wet-grinding liquid are, for example, excipients. The excipients are preferably sugars, sugar alcohols, etc., more preferably sucrose, mannitol, sorbitol, erythritol, xylitol, etc., and more preferably D-mannitol.
[0077] At least a part of the crystalline cellulose contained in the granulation liquid is derived from the wet-grinding liquid. The entire crystalline cellulose contained in the granulation liquid may be derived from the wet-grinding liquid.
[0078] The amount of microcrystalline cellulose derived from the wet-grinding liquid contained in the granulation liquid is, for example, from 1% by mass to 15% by mass based on the mass of the granulation liquid.
[0079] The granulation liquid may contain crystalline cellulose not derived from the wet-grinding liquid. The amount of crystalline cellulose not derived from the wet-grinding liquid contained in the granulation liquid is, for example, 0% by mass or more and 20% by mass or less based on the mass of the granulation liquid.
[0080] The amount of the additive contained in the granulation liquid is, for example, from 0% by mass to 15% by mass, based on the mass of the granulation liquid.
[0081] When preparing a granulation liquid, it is not preferable to subject the wet-grinding liquid to solid-liquid separation or drying treatment. That is, a dispersion obtained by subjecting the wet-grinding liquid to solid-liquid separation or drying treatment and redispersing the obtained solid content in a dispersion medium is not suitable as a granulation liquid.
[0082] In addition, the dispersion obtained by dispersing powdered crystalline cellulose (for example, commercially available crystalline cellulose) in a dispersion medium after dry-pulverizing it as necessary is also not suitable as a granulation liquid. Even if the median diameter D50 of the crystalline cellulose in the dispersion thus obtained is 25 μm or less, the desired effect cannot be obtained.
[0083] <Process (b)> The step (b) is selected from the step (b-1) and the step (b-2).
[0084] Step (b-1) is a step of wet-granulating the first granulation raw material containing a drug and an additive using the granulation liquid prepared in step (a) to obtain a first granulated product.
[0085] Step (b-2) is a step of wet-granulating a second granulation raw material containing an additive but not a drug using the granulation liquid prepared in step (a) to obtain a second granulated product.
[0086] Specific examples of the drug contained in the first granulation raw material are the same as those described above. The drug contained in the first granulation raw material may be one type or two or more types. The drug contained in the first granulation raw material may be in powder form or granular form. Granular drugs can be produced by a conventional method (for example, a known granulation method).
[0087] Powdered or granular drugs may be coated for the purpose of masking taste, odor, etc., controlling dissolution, etc. Examples of coating agents used for coating include ethyl cellulose, aminoalkyl methacrylate copolymer E, methacrylic acid copolymer L, dry methacrylic acid copolymer LD, methacrylic acid copolymer LD, methacrylic acid copolymer S, aminoalkyl methacrylate copolymer RS, aminoalkyl methacrylate copolymer RS, ethyl acrylate-methyl methacrylate copolymer, polyvinyl acetal-diethylaminoacetate, polyvinyl acetate resin, etc. Examples of plasticizers used in combination with the coating agent include diethyl sebacate, dibutyl sebacate, triethyl citrate, stearic acid, polyethylene glycol, triacetin, etc. Coating can be performed according to a conventional method.
[0088] Specific examples of additives contained in the first or second granulation raw material are the same as those described above. The additives contained in the first or second granulation raw material may be one type or two or more types. The additives contained in the first or second granulation raw material may be in powder form or granular form. Granular additives can be produced by a conventional method (for example, a known granulation method).
[0089] In one embodiment, the first or second granulation raw material contains an excipient and a disintegrant as additives. The excipient preferably contains D-mannitol, and the disintegrant preferably contains one or more selected from crospovidone, low-substituted hydroxypropyl cellulose, and croscarmellose sodium.
[0090] The method of wet granulation is not particularly limited as long as the granulation liquid prepared in step (a) is used. Examples of the method of wet granulation include fluidized bed granulation, stirring granulation, kneading granulation, extrusion granulation, and rolling granulation.
[0091] In one embodiment, the wet granulation method is a fluidized bed granulation method, in which the granulation liquid prepared in step (a) is sprayed onto a fluidized bed containing the first or second raw material to prepare a granulated product.
[0092] In order to improve the strength of the orally disintegrating tablet and effectively prevent the breakage of the orally disintegrating agent caused by impact during production, packaging, transportation, and packaging in hospitals, the amount of granulation liquid added to the first or second granulation raw material is adjusted to a predetermined amount. The predetermined amount is an amount in which the amount of crystalline cellulose derived from the wet grinding liquid contained in the orally disintegrating tablet is preferably 2.0% by mass or more based on the mass of the orally disintegrating tablet. The upper limit of the amount of crystalline cellulose derived from the wet grinding liquid contained in the orally disintegrating tablet can be appropriately adjusted depending on the amount of the drug, the amount of other additives, etc., and is, for example, 20% by mass or less.
[0093] The first or second granule obtained by wet granulation is preferably dried before step (c). Drying can be carried out according to a conventional method. The drying temperature is, for example, from 70° C. to 100° C., and the drying time is, for example, from 0.05 hours to 1 hour. Drying is preferably carried out so that the amount of moisture contained in the dried granule is from 0% by mass to 2.5% by mass, based on the mass of the dried granule.
[0094] After drying the first or second granules, it is preferable to size the granules before step (c). Size sizing can be performed according to a conventional method. For example, size sizing can be performed using a commercially available size sizing machine. The particle size of the granules after size sizing is, for example, 10 μm or more and 1000 μm or less.
[0095] <Process (c)> Step (c) is a step of compressing a first tableting raw material containing a first granule and optionally an additive, or a second tableting raw material containing a second granule, a drug and optionally an additive, to obtain an orally disintegrating tablet.
[0096] Specific examples of additives contained in the first or second tableting raw material are the same as those described above. The additives contained in the first or second tableting raw material may be one type or two or more types. The additives contained in the first or second tableting raw material may be in powder form or granular form. Granular additives can be produced by a conventional method (for example, a known granulation method).
[0097] Examples of additives contained in the first or second tableting raw material include a lubricant and a flow agent.
[0098] In one embodiment, the first or second tableting ingredient comprises, as an excipient, a lubricant, preferably magnesium stearate.
[0099] The first or second tableting raw material can be prepared by mixing predetermined components using, for example, a tumble mixer, a convection mixer or the like.
[0100] The second tableting raw material can be prepared, for example, by mixing the second granulated material and a drug, and then further mixing the additives.
[0101] Specific examples of the drug contained in the second tableting raw material are the same as those described above. The drug contained in the second tableting raw material may be one type or two or more types. The drug may be in powder form or granular form. Granular drugs can be produced by a conventional method (for example, a known granulation method). Powdered or granular drugs may be coated for the purpose of masking taste, odor, etc., controlling dissolution, etc. Specific examples of the coating agent used for coating are the same as those described above. Specific examples of the plasticizer used in combination with the coating agent are the same as those described above. Coating can be performed according to a conventional method.
[0102] Tableting (compression molding) can be performed by a conventional method, and the method of tableting is not particularly limited. Tableting can be performed using a tableting machine such as a rotary tableting machine or a single punch tableting machine. The molding pressure of the tableting machine can be appropriately adjusted so as to achieve the desired tablet hardness. The molding pressure of the tableting machine is, for example, 4 kN or more and 15 kN or less, preferably 4 kN or more and 10 kN or less. EXAMPLES
[0103] Example 1 25 g of powdered crystalline cellulose (Ceolas UF-711, Asahi Kasei Corporation) and 250 g of purified water were charged into a benchtop ball mill (Miniature Ball Mill AV Type, Asahi Rika Seisakusho Co., Ltd.) and wet-milled at a rotation speed of 500 rpm for 24 hours to obtain a wet-milled liquid (hereinafter referred to as "wet-milled liquid A"). The wet-milled liquid A was used as the granulation liquid in Example 1.
[0104] The median diameter D50 of the crystalline cellulose in the wet-pulverized liquid A (i.e., the crystalline cellulose after wet pulverization) was measured and found to be 11 μm. D50 is the particle size at which the cumulative volume is 50% in the volume-based particle size distribution obtained by the laser diffraction particle size distribution measurement method. The laser diffraction particle size distribution measurement method was performed using a laser diffraction particle size distribution measurement device (Mastersizer 3000, manufactured by Malvern Panalytical) under the following conditions. Light scattering model: Fraunhofer theory Refractive index: 0.050 Absorption Index: 0.000 Particle density: 1.00g / m 3 Dispersion medium: water Refractive index: 1.330 Stirring speed: 2500 rpm Sonication: No
[0105] Tablets having the composition shown in Table 1 were manufactured. Specifically, 6 g of istradeferin, 540 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were charged into a fluidized bed granulation dryer (FD-MP-01D, manufactured by POWREX) to form a fluidized bed, and then 378 g of the granulation liquid of Example 1 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 5 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (CORMIL QC-197S, manufactured by POWREX) equipped with a 0.991 mmφ screen to obtain a sized product. 250 g of the sized product and 2.5 g of magnesium stearate (PARTECK LUB MST, manufactured by Merck KGaA) were charged into a vinyl bag and mixed. The resulting mixture was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with an 8 mmφ flat punch, and compressed under a pressure of 10 kN to obtain tablets (mass per tablet: 200 mg).
[0106] [Table 1]
[0107] Example 2 In 630 g of the wet-milled liquid A obtained in Example 1, 45 g of D-mannitol (PEARLITOL 160C, manufactured by Roquette) was dissolved to obtain a granulation liquid of Example 2.
[0108] Tablets having the composition shown in Table 1 were manufactured. Specifically, 855 g of D-mannitol (PEARLITOL 160C, manufactured by Rocket) and 50 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex) to form a fluidized bed, and then 675 g of the granulation liquid of Example 2 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 6 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (Comil QC-197S, manufactured by Powrex) equipped with a 0.991 mmφ screen to obtain a sized product. 294 g of the sized product and 3 g of istradeferin were placed in a vinyl bag and mixed. 297 g of the resulting mixture and 3 g of magnesium stearate were placed in a vinyl bag and mixed. The mixture obtained was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with a flat punch of 8 mm diameter, and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg). Of the 180 mg of D-mannitol contained in one tablet, the amount of D-mannitol derived from the granulation liquid of Example 2 was 9 mg.
[0109] Example 3 In 1260 g of the wet-milled liquid A obtained in Example 1, 90 g of D-mannitol (PEARLITOL 160C, manufactured by Roquette) was dissolved to obtain a granulation liquid of Example 3.
[0110] Tablets having the composition shown in Table 2 were manufactured. Specifically, 6 g of istradeferin, 408 g of D-mannitol (PEARLITOL 160C, manufactured by Rocket Co., Ltd.) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP Co., Ltd.) were charged into a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex Co., Ltd.) to form a fluidized bed, and then 1350 g of the granulation liquid of Example 3 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 5 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (Comil QC-197S, manufactured by Powrex Co., Ltd.) equipped with a 0.991 mmφ screen to obtain a sized product. 301 g of the sized product and 3.0 g of magnesium stearate were charged into a vinyl bag and mixed. The mixture obtained was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with a flat punch of 8 mm diameter, and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg). Of the 166 mg of D-mannitol contained in one tablet, the amount of D-mannitol derived from the granulation liquid of Example 3 was 30 mg.
[0111] [Table 2]
[0112] Example 4 25 g of powdered crystalline cellulose (Ceolas UF-711, manufactured by Asahi Kasei Corporation) and 250 g of purified water were placed in a benchtop ball mill (Mini Ball Mill AV Type, manufactured by Asahi Rika Seisakusho) and wet-ground at a rotation speed of 500 rpm for 5 hours to obtain a wet-ground liquid (hereinafter referred to as "wet-ground liquid B").
[0113] The median diameter D50 of the crystalline cellulose in the wet-grinding solution B (i.e., the crystalline cellulose after wet-grinding) was measured and found to be 21 μm. D50 was measured in the same manner as in Example 1.
[0114] 27 g of D-mannitol was dissolved in 378 g of the wet grinding liquid B to obtain the granulating liquid of Example 4.
[0115] Tablets having the composition shown in Table 1 were manufactured. Specifically, 6 g of istradeferin, 513.1 g of D-mannitol (PEARLITOL 160C, manufactured by Rocket Co., Ltd.) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP Co., Ltd.) were charged into a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex Co., Ltd.) to form a fluidized bed, and 405 g of the granulation liquid of Example 4 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 5 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (Comil QC-197S, manufactured by Powrex Co., Ltd.) equipped with a 0.991 mmφ screen to obtain a sized product. 250 g of the sized product and 2.5 g of magnesium stearate were charged into a vinyl bag and mixed. The mixture obtained was compressed and molded at a pressure of 10 kN using a tablet press with a flat 8 mm diameter punch to obtain tablets (weight per tablet: 200 mg). Of the 180 mg of D-mannitol contained in each tablet, the amount of D-mannitol derived from the granulation liquid of Example 4 was 9 mg.
[0116] Comparative Example 1 Powdered crystalline cellulose (Ceolas UF-711, Asahi Kasei) was put into a jet mill (Co-JET SYSTEM αmk-III, Seishin Enterprise Co., Ltd.) and dry-milled. The median diameter D50 of the crystalline cellulose after dry-milling was measured to be 6 μm. D50 was measured by a laser diffraction particle size distribution measurement method using a laser diffraction particle size distribution measurement device (Microtrac MT3300EX II, Microtrac Bell Co., Ltd.) under the following conditions. Dry Measurement Dispersion pressure: 0.1MPa Particle name: GLASS Particle permeability: transparent Particle refractive index: 1.51 Particle shape: true spherical Solvent:AIR Solvent refractive index: 1.00
[0117] Tablets having the composition shown in Table 1 were produced. Specifically, 6 g of istradeferin, 540 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET), 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) and 18 g of crystalline cellulose after dry grinding were charged into a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex Corporation) to form a fluidized bed, and then 342 g of purified water was sprayed onto the fluidized bed. The resulting granulated product was dried at 90°C for 5 minutes to obtain a dried granulated product. Tablets were obtained in the same manner as in Example 1 using the obtained dried granulated product.
[0118] Comparative Example 2 18 g of powdered crystalline cellulose (CEOLUS UF-711, Asahi Kasei Corporation) was dispersed in 342 g of water to obtain a crystalline cellulose dispersion (hereinafter referred to as "crystalline cellulose dispersion C"). The crystalline cellulose dispersion C was used as the granulation liquid in Comparative Example 2. When obtaining the crystalline cellulose dispersion C, the crystalline cellulose was not subjected to dry or wet grinding.
[0119] The median diameter D50 of the crystalline cellulose in the crystalline cellulose dispersion C was measured and found to be 37 μm. D50 was measured in the same manner as in Example 1.
[0120] Tablets having the composition shown in Table 1 were produced. Specifically, 6 g of istradeferin, 540 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were charged into a fluidized bed granulation dryer (FD-MP-01D, manufactured by POWREX) to form a fluidized bed, and then 360 g of the granulation liquid of Comparative Example 2 was sprayed onto the fluidized bed. The resulting granulated material was dried at 90° C. for 4 minutes to obtain a dried granulated material. Tablets were obtained using the obtained dried granulated material in the same manner as in Example 1.
[0121] Comparative Example 3 18 g of powdered crystalline cellulose (VIVAPUR105, manufactured by JRS PHARMA) was dispersed in 342 g of water to obtain a crystalline cellulose dispersion (hereinafter referred to as "crystalline cellulose dispersion D"). Note that when obtaining crystalline cellulose dispersion D, the crystalline cellulose was not subjected to dry or wet grinding.
[0122] The median diameter D50 of the crystalline cellulose in the crystalline cellulose dispersion D was measured and found to be 17 μm. D50 was measured in the same manner as in Example 1.
[0123] In 360 g of the crystalline cellulose dispersion D, 27 g of D-mannitol (PEARLITOL 160C, manufactured by Roquette) was dissolved to obtain a granulation liquid of Comparative Example 3.
[0124] Tablets having the composition shown in Table 1 were produced. Specifically, 6 g of istradefylline, 513 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were charged into a fluidized bed granulation dryer (FD-MP-01D, Powrex) to form a fluidized bed, and then 387 g of the granulation liquid of Comparative Example 3 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 3 minutes to obtain a dried granulation product. Using the resulting dried granulation product, tablets were obtained in the same manner as in Example 1. Of the 180 mg of D-mannitol contained in one tablet, 9 mg of D-mannitol was derived from the granulation liquid of Comparative Example 3.
[0125] Comparative Example 4 A granulation liquid of Comparative Example 4 was obtained by dissolving 9 g of D-mannitol in 126 g of the wet-milled liquid A obtained in Example 1.
[0126] Tablets having the composition shown in Table 3 were manufactured. Specifically, 6 g of istradeferin, 543 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET) and 30 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a fluidized bed granulation dryer (FD-MP-01D, manufactured by POWREX) to form a fluidized bed, and then 135 g of the granulation liquid of Comparative Example 4 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 3 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (CORMIL QC-197S, manufactured by POWREX) equipped with a 0.991 mmφ screen to obtain a sized product. 301 g of the sized product and 3 g of magnesium stearate were added to a vinyl bag and mixed. The mixture obtained was compressed and molded at a pressure of 10 kN using a tablet press with a flat 8 mm diameter punch to obtain tablets (weight per tablet: 200 mg). Of the 184 mg of D-mannitol contained in each tablet, the amount of D-mannitol derived from the granulation liquid of Comparative Example 4 was 3 mg.
[0127] [Table 3]
[0128] The characteristics of Examples 1 to 4 and Comparative Examples 1 to 4 are summarized in Table 4.
[0129] [Table 4]
[0130] [Test Example 1] The physical properties of each of the tablets obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were evaluated as follows.
[0131] (1) Tablet thickness The thickness of five tablets was measured using a dial thickness gauge (manufactured by Mitutoyo Co., Ltd.) and the average value was calculated. The results are shown in Table 5.
[0132] (2) Tablet hardness The hardness of two tablets was measured using a tablet hardness tester (PTB-311E, manufactured by PHARMA TEST Co., Ltd.) and the average value was calculated. The results are shown in Table 5.
[0133] (3) Disintegration test A circular filter paper with a diameter of 55 mm was placed in a plastic petri dish, and 2 mL of colored water (10 mg / mL Yellow No. 5 aqueous solution) was soaked into the filter paper. One tablet was gently placed in the center of the filter paper, and the time it took for the colored water to penetrate the entire tablet surface (water absorption time) was measured. The water absorption times of two tablets were measured and the average value was calculated. The results are shown in Table 5.
[0134] (4) Friability test The friability test was performed according to the 17th edition of the Japanese Pharmacopoeia Reference Information "G6. Preparation-related Tablet Friability Test Method". After 32 or 33 tablets (32 tablets in Example 3, Example 5, and Comparative Example 4, and 33 tablets in other Examples and Comparative Examples) were conditioned for 5 hours in a 25°C / 60% RH environment, the powder adhering to each tablet was removed, the total mass (W) of all tablets was precisely measured, and the tablets were placed in a drum. After 25 rotations of the drum, all tablets were taken out. The powder adhering to each tablet was removed, and the total mass (Wt) of all tablets was precisely measured. The friability was calculated based on the following formula (1). The results are shown in Table 5.
[0135]
number
[0136] (5) Visual inspection After the friability test, the tablets were visually evaluated according to the following criteria, and the numbers of good, slightly defective, and seriously defective tablets were counted. The results are shown in Table 5.
[0137] Good product: The total area of the chipped areas is 0.50 mm 2 less than Minor defects: The total area of the chipped areas is 0.50 mm 2 More than 1.0mm 2 less than Severely defective: The total area of the chipped areas is 1.0 mm 2 End
[0138] [Table 5]
[0139] As shown in Table 5, in Examples 1 to 4, orally disintegrating agents having a hardness of 40N or more and a friability of 0.1% or less were obtained, whereas in Comparative Examples 1 to 4, orally disintegrating agents having a hardness of 40N or more and a friability of 0.1% or less were not obtained. Also, as shown in Table 5, the non-defective product rates after the friability test of the orally disintegrating agents obtained in Examples 1 to 4 were significantly higher than the non-defective product rates after the friability test of the orally disintegrating agents obtained in Comparative Examples 1 to 4. From these results, it was found that in a method for producing an orally disintegrating tablet by tableting a tableting raw material containing a granulated product obtained by wet granulation, the strength of the orally disintegrating tablet produced is improved by performing wet granulation using a granulation liquid containing a wet pulverization liquid obtained by wet pulverizing crystalline cellulose so that the amount of crystalline cellulose derived from the wet pulverization liquid contained in the orally disintegrating tablet is 2.0% by mass or more based on the mass of the orally disintegrating tablet.
[0140] Example 5 In 630 g of the wet-milled liquid A obtained in Example 1, 45 g of D-mannitol (PEARLITOL 160C, manufactured by Roquette) was dissolved to obtain a granulation liquid of Example 5.
[0141] Tablets having the composition shown in Table 6 were manufactured. Specifically, 855 g of D-mannitol (PEARLITOL 160C, manufactured by ROCKET) and 50 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a fluidized bed granulation dryer (FD-MP-01D, manufactured by POWREX) to form a fluidized bed, and then 675 g of the granulation liquid of Example 5 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90°C for 6 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (CORMIL QC-197S, manufactured by POWREX) equipped with a 0.991 mmφ screen to obtain a sized product. 288 g of the sized product and 9 g of domperidone were placed in a vinyl bag and mixed. 297 g of the resulting mixture and 3 g of magnesium stearate were placed in a vinyl bag and mixed. The mixture obtained was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with a 8 mmφ flat punch and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg). Of the 176.4 mg of D-mannitol contained in each tablet, 8.8 mg was derived from the granulation liquid of Example 5.
[0142] [Table 6]
[0143] Example 6 In 630 g of the wet-milled liquid A obtained in Example 1, 45 g of D-mannitol (PEARLITOL 160C, manufactured by Roquette) was dissolved to obtain a granulation liquid of Example 6.
[0144] Tablets having the composition shown in Table 7 were manufactured. Specifically, 855 g of D-mannitol (PEARLITOL 160C, manufactured by Rocket) and 50 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex) to form a fluidized bed, and then 675 g of the granulation liquid of Example 6 was sprayed onto the fluidized bed, and the resulting granulation was dried at 90 ° C for 6 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (Comil QC-197S, manufactured by Powrex) equipped with a 0.991 mmφ screen to obtain a sized product. 282 g of the sized product and 15 g of ethenzamide were put into a vinyl bag and mixed. 297 g of the resulting mixture and 3 g of magnesium stearate were put into a vinyl bag and mixed. The mixture obtained was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with a 8 mmφ flat punch and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg). Of the 172.6 mg of D-mannitol contained in each tablet, 8.6 mg was derived from the granulation liquid of Example 6.
[0145] [Table 7]
[0146] [Test Example 2] The physical properties of each of the tablets obtained in Examples 5 and 6 were evaluated in the same manner as in Test Example 1. The results are shown in Table 8.
[0147] [Table 8]
[0148] As shown in Table 8, orally disintegrating agents having a hardness of 40N or more and a friability of 0.1% or less were obtained in Examples 5 and 6. Also, as shown in Table 8, the non-defective product rates after the friability test of the orally disintegrating agents obtained in Examples 5 and 6 were significantly higher than the non-defective product rates after the friability test of the orally disintegrating agents obtained in Comparative Examples 1 to 4. From these results, it was found that the effects demonstrated in Examples 1 to 4 can be obtained regardless of the type of drug contained in the orally disintegrating agent.
[0149] [Reference example 1] The wet-grinding liquid A obtained in Example 1 was used as a granulation liquid in Reference Example 1.
[0150] Tablets having the composition shown in Table 9 were manufactured. Specifically, 918 g of D-mannitol (PEARLITOL 25C, manufactured by ROCKET) and 50 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a fluidized bed granulation dryer (FD-MP-01D, manufactured by POWREX) to form a fluidized bed, and then 440 g of the granulation liquid of Reference Example 1 was sprayed onto the fluidized bed, and the resulting granulation was dried at 80°C for 13 minutes to obtain a dried granulation product. The resulting dried granulation product was sized using a granulator (CORMIL QC-197S, manufactured by POWREX) equipped with a 0.991 mmφ screen to obtain a sized product. 250 g of the sized product and 2.5 g of magnesium stearate were added to a vinyl bag and mixed. The resulting mixture was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with an 8 mmφ flat punch, and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg).
[0151] [Table 9]
[0152] [Reference example 2] Tablets having the composition shown in Table 10 were manufactured. Specifically, 4512 g of D-mannitol (PEARLITOL 25C, manufactured by Rocket) and 240 g of crospovidone (Polyplasdone XL-10, manufactured by ISP) were added to a stirring and mixing granulator (Vertical Granulator VG-25, manufactured by Powrex), and then 950 g of purified water was sprayed. The resulting granules were wet-granulated using a granulator (Comil QC-197S, manufactured by Powrex) equipped with a 9.525 mmφ screen, and then placed in a fluidized bed granulation dryer (FD-MP-01D, manufactured by Powrex) and dried at 80 ° C. until the temperature of the granules reached 45 ° C. The resulting dried granules were granulated using a granulator (Comil QC-197S, manufactured by Powrex) equipped with a 0.991 mmφ screen to obtain a granulated product. 198 g of the sized product and 2.0 g of magnesium stearate were placed in a vinyl bag and mixed. The resulting mixture was placed in a rotary tablet press (VIRGO (0512SS2AZ), manufactured by Kikusui Seisakusho) equipped with an 8 mmφ flat punch and compressed under a pressure of 10 kN to obtain tablets (weight per tablet: 200 mg).
[0153] [Table 10]
[0154] [Test Example 3] For each of the tablets obtained in Reference Examples 1 and 2, the physical properties were evaluated in the same manner as in Test Example 1, except that the conditions for the friability test were changed. The results are shown in Table 11.
[0155] The friability test in Test Example 3 was performed according to the 17th Revised Japanese Pharmacopoeia Reference Information "G6. Preparation-related Tablet Friability Test Method". After 32 or 33 tablets (32 in Reference Example 1, 33 in Reference Example 2) were conditioned for 5 hours in a 25°C / 60% RH environment, the powder adhering to each tablet was removed, the total mass (W) of all tablets was precisely measured, and the tablets were placed in a drum equipped with a stainless steel (SUS) plate. After rotating the drum 100 times, all tablets were taken out. The powder adhering to each tablet was removed, and the total mass (Wt) of all tablets was precisely measured. As in Test Example 1, the friability was calculated based on formula (1).
[0156] [Table 11]
[0157] As shown in Table 11, the addition of crystalline cellulose increased hardness and decreased friability.
Claims
1. The following steps: (a) A step of preparing a granulation liquid containing a wet grinding liquid obtained by wet grinding crystalline cellulose; (b) A step of wet granulating a first granulation material containing a drug and an additive using the granulation liquid to obtain a first granule, or a step of wet granulating a second granulation material containing an additive but not a drug using the granulation liquid to obtain a second granule; and (c) A step of compressing a first tableting material containing the first granules and optionally an additive, or a second tableting material containing the second granules, a drug and optionally an additive, to obtain an orally disintegrating tablet. A method for manufacturing orally disintegrating tablets, including, The manufacturing method wherein the amount of crystalline cellulose derived from the wet pulverizing liquid contained in the orally disintegrating tablet is 2.0% by mass or more, based on the mass of the orally disintegrating tablet.
2. The manufacturing method according to claim 1, wherein the median diameter D50 of the crystalline cellulose in the wet grinding liquid is 25 μm or less.
3. The manufacturing method according to claim 1 or 2, wherein the degree of abrasion of the orally disintegrating tablet is 1.0% or less.
4. The manufacturing method according to claim 1 or 2, wherein the first or second granulation raw material includes an excipient and a disintegrant as the additive.
5. The manufacturing method according to claim 4, wherein the excipient comprises D-mannitol.
6. The manufacturing method according to claim 4, wherein the disintegrant comprises one or more selected from crospovidone, low-substituted hydroxypropylcellulose, and croscarmellose sodium.
7. The manufacturing method according to claim 1 or 2, wherein the first or second tableting raw material includes a lubricant as the additive.
8. The manufacturing method according to claim 7, wherein the lubricant comprises magnesium stearate.
9. The manufacturing method according to claim 1 or 2, wherein the drug is istradefelin, domperidone, or ethenzamide.